Investigating the Service life of asphalt pavement in a sample of Ramadi district roads - awaad, Kalid (Anbar Journal of Engineering Sciences, 2017)
A sample of 50 randomly selected rural and urban roads of Ramadi district were observed for asphalt pavement Distresses. Three main types of Distresses were considered; rutting, cracks and pavement separation. In addition, different other Distresses types that were observed were grouped in one category named "Other". For each road, information about the age of the pavement was recorded. Kaplan-Meier method was carried out in order to understand the Remain time before pavement deterioration as well as to compare pavement service life with respect to the type of Distress. Results of this research revealed significant differences between pavement service life corresponding to the type of Distress. Pavement service life appeared to last less than 20 months when all the mentioned types of Distresses are occurred on the road